Handbook of PVC pipe design and construction (Industrial Press, 2012)
Annotation A new, expanded edition of the authoritative handbook now available from Industrial Press for the first time.
Keywords: Pipe, Plastic -- Design and construction.; Pipelines.; elektronické knihy; electronic books